Formulasi Sediaan Sampo Ekstrak Bunga Chamomile dengan Hidroksi Propil Metil Selulosa sebagai Pengental - FAIZATUN FAIZATUN; KARTININGSIH KARTININGSIH; LILYANA LILIYANA (Fakultas Farmasi Universitas Pancasila, 2008)
Chamomile (Chamomilla recucita L.) that contain apigenin as an active substance are known as hair-lightening agent. The application of these flowers as such is not convenient, so the incorporation of its extract in shampoos - for cleaning of both scalp and hair - gives a better outcome. In this study, six formulas Were applied, each containing 5% of chamomile extract with different concentrations of HPMC (Methocel® F4M) and other additives. The shampoos were evaluated during a six Week-storage on their physico-chemical properties (pH, viscosity, rheological characteristic at 28-30°C [room temperaturel, 40°C, and 6-7°C [chilled temperature], surface tension, foam-forming in hard and distilled water as Well as sensory properties [discoloration, odor, homo genenity]. The results showed that HPMC of 2% gave an optimum viscosity, no discoloration, no detected change on homogenenity as Well as odor until the end of six-Week storage. The viscosity the shampoo with 2% HPMC at 28-30°C was 2060.00-2080.00 cPs,at 40°C 1040.00-1080.00 cPs, and at 6-7°C 2420.00-2480.00 cPs. Having rheological characteristic of pseudoplastic, the shampoo’s surface tension Was 28.99-29.88 dyne/cin, with density ranged 1,0428- 1.0459, pH 6.26-6.34, height of foam in hard Water ranged 3.30-3.45 cm and in distilled 3.40-3.60 cm. The density, surface tension, and pH of the shampoo were in agreement with the requirements. Key words: Hydroxypropyl methyl cellulose, chamomile, shampoo, viscosity.